Intimate letters of young lovers - Garon, Bob (Pasig City, Philippines : Anvil Publications, 1995)
Most often, the root causes of failed marriages can be found in the days when lovers least expected. It is during courtship, during the time preceding marriage that hints of trouble have already surfaced.
1. The boss wants marriage -- 2. her boy copped out -- 3. Annulment still possible -- 4. Knocked up, and let down -- 5. Torn between heart and mind -- 6. Waiting wont hurt -- 7. Persistent guilt feeling -- 8. Put your foot down -- 9. Child abuse victim -- 10. Blind to reality -- 11. Dilemma over inter-racial marriage -- 12. The love trap -- 13. Love calls for trust -- 14. forget him and move on -- 15. Insistence is dangerous -- 16. Demand openness -- 17. Confused unwed mother -- 18. He wants his space -- 19. too young at 21 -- 20. Rough sailing relationship -- 21. choosing Mr. Right -- 22. find out the truth -- 23. torn between two married men -- 24. He's a trap -- 25. Defer your married plans -- 26. Be less demonstrative -- 27. The guy's too shy -- 28. Ponder and decide -- 29. Two loves has she -- 30. Unworthy guy -- 31. Disoriented girl -- 32. When to hold marriage plan -- 33. You're for kicks -- 33. One big lie is enough -- 34. Young man in a hurry -- 35. Know his status -- 36. Marriage is out for the question -- 37. Never too old -- 38. Perilous affair -- 39. Torn between two loved ones -- 40. Single mom needs a job -- 41. Falling and staying in love -- 42. Weighing two worlds -- 43. Long distance courtship -- 44. A giant leap -- 45. Childish couple -- 46. Kissing cousins -- 47. The pain of rejection -- 48. Two relationships -- 49. Mother need not interfere in your married life -- 50. No communication, no relation -- 51. You have not yet really experienced motherhood -- 52. Break off for a while -- 53. Can you blame her? -- 54. Don't grieve forever -- 55. Find out more about him -- 56. He loves you but sleeps with her? -- 57. Your heart needs to cool off -- 58. Torn between two lovers -- 59.If he loves you, he'll move out -- 60. Get out quietly while you have the chance -- 61. Your chances are zero -- 62. Petting and sex do not guarantee love -- 63. Give him up... you will love again -- 64. Walk away unless he gets his life together -- 65. It's your head that keeps you balance -- 66. He's getting free sex -- 67. She must suspect you love her -- 68. The Japayuki is playing with you -- 69. Weigh your options carefully .
Keywords: INTERPERSONAL RELATIONS